The chromosome‐scale reference genome of safflower (Carthamus tinctorius) provides insights into linoleic acid and flavonoid biosynthesis. Issue 9 (8th April 2021) - Wu, Zhihua; Liu, Hong; Zhan, Wei; Yu, Zhichao; Qin, Erdai; Liu, Shuo; Yang, Tiange; Xiang, Niyan; Kudrna, Dave; Chen, Yan; Lee, Seunghee; Li, Gang; et al.
Summary: Safflower ( Carthamus tinctorius L.), a member of the Asteraceae, is a popular crop due to its high linoleic acid (LA) and flavonoid (such as hydroxysafflor yellow A) contents. Here, we report the first high‐quality genome assembly (contig N50 of 21.23 Mb) for the 12 pseudochromosomes of safflower using single‐molecule real‐time sequencing, Hi‐C mapping technologies and a genetic linkage map. Phyloge nomic analysis showed that safflower diverged from artichoke ( Cynara cardunculus ) and sunflower ( Helianthus annuus ) approximately 30.7 and 60.5 million years ago, respectively. Comparative genomic analyses revealed that uniquely expanded gene families in safflower were enriched for those predicted to be involved in lipid metabolism and transport and abscisic acid signalling. Notably, the fatty acid desaturase 2 (FAD2) and chalcone synthase (CHS) families, which function in the LA and flavonoid biosynthesis pathways, respectively, were expanded via tandem duplications in safflower. CarFAD2‐12 was specifically expressed in seeds and was vital for high‐LA content in seeds, while tandemly duplicated CarFAD2 genes were up‐regulated in ovaries compared to CarFAD2‐12, which indicates regulatory divergence of FAD2 in seeds and ovaries. CarCHS1, CarCHS4 and tandem‐duplicated CarCHS5 ˜ CarCHS6, which were up‐regulated compared to other CarCHS members at early stages, contribute to the accumulation of major flavonoids in flowers. In addition, our data reveal multiple alternative splicing events in gene families related to fatty acid and flavonoid biosynthesis. Together, these results provide a high‐quality reference genome and evolutionary insights into the molecular basis of fatty acid and flavonoid biosynthesis in safflower.